Shoot culture of Bacopa monnieri: standardization of explant, vessels and bioreactor for growth and antioxidant capacity - Jain, Neelam (Springer-Verlag, 2012)
Standardization of biomass production in different vessels and bioreactor using explants and media for growth, total phenolic content and antioxidant capacity of shoot culture of Bacopa monnieri is described. Maximum number of shoots per explant, higher explants response irrespective of the type of explants, and higher shoot length was obtained on MS medium containing BAP (2.5 mg l(−1)) and IAA (0.01 mg l(−1)) with 3 % sucrose. This medium was selected by varying BAP concentration and recorded optimal for shoot culture on gelled medium. The condition of 0.5 cm explant size and 20 explant/40 ml (1 explant/2 ml) was optimal for high explant response, number of shoots per explant regenerated and shoots length. Among the different vessels used, maximum growth index was achieved in Growtek bioreactor (10.0) followed by magenta box (9.16), industrial glass jar (7.7) and conical flask (7.2). The cultures grown in conical flask (100 ml) were used as control. The total phenolic content and antioxidant capacity of in vitro grown plants was higher to that recorded for in vivo material. Among in vitro regenerated plants, the activity was maximal in the tissues grown in 250 ml conical flask. The most critical function for vessels is to support the optimum profusion (growing area for maximum growth) of shoots and for B. monnieri, Growtek bioreactor supported 1980 shoots l(−1) medium as compared to control (938 shoots l(−1)). Growtek bioreactor was considered effective system to produce B. monnieri biomass in culture without loss of antioxidant properties.